Student engagement in the Flipped Classroom model implemented in online learning - Teresa Ribeirinha; Bento Silva (Grupo de Investigación "Nodo Educativo" / Red Universitaria de Tecnología Educativa (RUTE), 2024)
Student engagement is a determinant factor of students' academic success, with added relevance for online learning. The aim of this study was to analyse students' cognitive, affective, and behavioural engagement in a pedagogical proposal based on the Flipped Classroom model, with Portuguese secondary school students. The study, conducted during the COVID-19 pandemic, combined asynchronous and synchronous lessons divided into learning episodes (Summary, Quiz and Rooms). Mixed methods were used to analyse students' discourses, behaviours, perceptions of the experience and academic performance. The results showed that the proposal enhanced a high level of behavioural engagement in the students as expressed by the indicators of task completion, peer interaction and participation. Students showed higher levels of cognitive engagement in the Rooms episodes as they were conducive to peer interaction, explicitness of knowledge and reflection facilitated by interaction with the teacher. Satisfaction was the most prominent indicator of student affective engagement. This study offers a better understanding of the factors that influence student engagement in the Flipped Classroom model and suggests practical implications for enhancing it in online learning.